Economic Stress and Domestic Violence: Examining the Impact of Mortgage Foreclosures on Incidents Reported to the Police. (December 2015) - Pattavina, April; Socia, Kelly M.; Zuber, Malgorzata J.
The empirical research on the relationship between mortgage foreclosures and crime continues to evolve, and, with few exceptions, the results generally show that there is a relationship between community measures of mortgage foreclosure and crime levels. Lacking in this literature are studies that considered how foreclosures may impact domestic violence. For many families, home mortgages have significant meaning as an indicator of financial stability and represent a long-term commitment to a community through home ownership and the accompanying social and financial investments. Families who are threatened with the loss of their home to foreclosure experience a decrease in their financial status, and the stress triggered by the crisis may place them at greater risk for family violence. In this study, we examine the relationship between mortgage foreclosures and family violence. Using longitudinal panel data for Massachusetts cities and towns, our study focuses specifically on the years 2005–2009, the period that includes the Great Recession. We find that after controlling for other community indicators of economic health, higher levels of monthly mortgage foreclosures lead to higher levels of domestic violence.